Celebrating Palouse country : a history of the landscape in text and images - Scheuerman, Richard D., 1951- (Basalt Books, 2024)
"Travel through time among the Palouse Country's beauty and expanse, starting with its First Peoples. This 30th anniversary edition of an exceptional author and photographer collaboration presents an updated Palouse history enriched with spectacular new images"--